1994
DOI: 10.3109/03009749409103729
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Psychiatric Symptoms in Patients with Systemic Lupus Erythematosus

Abstract: The purpose of this review was to explore the probable etiologies of psychiatric problems in patients with SLE. Although instances of psychosis generally are attributed to disease pathophysiology, the precise mechanism for this problem remains speculative. The etiology of non-psychotic psychiatric complaints is even less clear. Overall, it is likely that psychiatric complaints in patients with SLE are attributable to numerous factors including acquired brain dysfunction, organ system dysfunction, iatrogenic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 68 publications
0
14
2
Order By: Relevance
“…In contrast, we did not find the associations reported in several studies (Iverson & Anderson, 1994;Kozora, Ellison, & West, 2006;Ward, Marx, & Barry, 2004), between SLE activity (SLEDAI) or damage (SLICC) and depression. Our findings suggest that it is the impact of SLE on lived experience, rather than the illness per se, that carries a depressogenic effect.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, we did not find the associations reported in several studies (Iverson & Anderson, 1994;Kozora, Ellison, & West, 2006;Ward, Marx, & Barry, 2004), between SLE activity (SLEDAI) or damage (SLICC) and depression. Our findings suggest that it is the impact of SLE on lived experience, rather than the illness per se, that carries a depressogenic effect.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the association found between physical illness markers and depression in several studies (Iverson & Anderson, 1994;Nery et al, 2007;Ward, Marx, & Barry, 2004) is not to be discounted, particularly as our data, which is derived from routine lab tests, do not include such depressionrelated measurements as C-reactive protein and cytokines. The inconsistent pattern of results regarding the associations between SLE activity or damage and depression may be accounted for by the mediating role of a subjective sense of distress, as evidenced by HRQol or illness intrusiveness.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Systemic lupus erythematous is also a multi-organ systemic vasculitis, which is known to affect the cerebral nervous system (CNS), causing various neuropsychiatric symptoms [18,19]. Multiple areas of hypoperfusion have been shown on SPECT studies of lupus patients positive for neuropsychiatric symptoms [20].…”
Section: Discussionmentioning
confidence: 99%
“…9 Despite the plethora of research articles, clear delineation of variables that are causally connected to psychiatric symptomatology in patients with SLE remains elusive. 10,11 People with SLE frequently experience psychiatric problems such as organic mental syndromes or disorders, psychotic disorders, mood disorders, anxiety disorders, sleep disturbances or sexual dysfunctions.l° There have been explicit assumptions in the literature that psychiatric disturbance in patients with SLE is a direct manifestation of the disease process,l2-'6 while others question this assumption. [17][18][19] In a methodological review of the literature on psychiatric disturbance associated with SLE, Iversonlo concluded that the available studies lacked the empirical rigor to estimate the prevalence of these problems or to assert that psychiatric symptoms are causally related to SLE pathophysiology.…”
Section: Introductionmentioning
confidence: 99%